The Importance Of Working On Sentences In The Development Of Oral And Written Speech Of Primary Class Students - Xoliqova Matluba (Genius Journals, 2023)
This article provides an idea of the importance of working on a sentence in the cultivation of oral and written speech of Primary School students and the role of tone in the formation of a sentence.
Keywords: sentence; oral and written speech; primary class